Social Mobility in Developing Countries Concepts, Methods, and Determinants - Iversen, Vegard; Krishna, Anirudh; Sen, Kunal (Oxford University Press, 2021)
Social mobility is the hope of economic development and the mantra of a good society. There are disagreements about what constitutes social mobility, but there is broad agreement that people should have roughly equal chances of success regardless of their economic status at birth. Concerns about rising inequality have engendered a renewed interest in social mobility-especially in the developing world. However, efforts to construct the databases and meet the standards required for conventional analyses of social mobility are at a preliminary stage and need to be complemented by innovative, conceptual, and methodological advances. If forms of mobility have slowed in the West, then we might be entering an age of rigid stratification with defined boundaries between the always-haves and the never-haves-which does not augur well for social stability. Social mobility research is ongoing, with substantive findings in different disciplines-typically with researchers in isolation from each other. A key contribution of this book is the pulling together of the emerging streams of knowledge. Generating policy-relevant knowledge is a principal concern. Three basic questions frame the study of diverse aspects of social mobility in the book. How to assess the extent of social mobility in a given development context when the datasets by conventional measurement techniques are unavailable? How to identify drivers and inhibitors of social mobility in particular developing country contexts? How to acquire the knowledge required to design interventions to raise social mobility, either by increasing upward mobility or by lowering downward mobility?